Factors influencing therapeutic efficacy of denosumab against osteoporosis in systemic lupus erythematosus - Sung-Hwan Park; Seung-Ki Kwok; Wan-Uk Kim; Ji Hyeon Ju; Jiwon Yang; Youngjae Park; Jennifer Jooha Lee (Lupus Science and Medicine)
Objective Osteoporosis is a common comorbidity in patients with SLE, and bone loss in patients with SLE has a multifactorial aetiology. This study aimed to evaluate the therapeutic efficacy of denosumab in patients with SLE with osteoporosis and to analyse the factors influencing therapeutic efficacy.Methods A total of 166 patients with SLE with osteoporosis who initiated denosumab between January 2016 and December 2023 were included. Changes in the T-score and areal bone mineral density (BMD) at the lumbar spine, total hip and femur neck from denosumab initiation to 12 months were measured. Correlation analysis was performed between the degree of BMD improvement and covariates including SLE-specific factors such as SLE duration, SLE Disease Activity Index 2000 (SLEDAI-2K) score, glucocorticoid dose and hydroxychloroquine use. Multiple linear regression analysis was conducted to identify predictors of the therapeutic efficacy of denosumab.Results Denosumab significantly increased BMD and decreased bone turnover markers at 12 months compared with baseline. The degree of BMD improvement revealed a significant negative correlation with SLEDAI-2K score, hydroxychloroquine use, prior osteoporosis treatment and baseline BMD values. In contrast, body mass index and c-telopeptide of collagen type 1 levels were positively correlated with the degree of BMD improvement. Higher baseline BMD values, SLEDAI-2K scores and hydroxychloroquine use were significant predictors of attenuated BMD improvement.Conclusions Our study suggests that denosumab is an effective treatment option for osteoporosis in patients with SLE. The therapeutic efficacy of denosumab can be predicted by baseline BMD values, SLEDAI-2K scores and hydroxychloroquine use.